Integrated resource planning as a strategy for implementing water management in Brazil (Research, Society and Development, 2021)
This investigation aims to analyze integrated resource planning as a strategy for implementing water management in Brazil. The National Water Agency and the National Water Security Secretariat began in 2019, the construction of the new National Water Resources Plan, which contains strategies for the institutional articulation of the plan, which has a horizon until the year 2040. It is in this perspective, that this article seeks to collaborate through the contribution of integrated water resources planning as an instrument in favor of Brazilian water management. The methodology of this study is supported by a bibliographic and documentary survey on the categories Integrated Planning of Resources and Management of Water Resources in Brazil, in order to enable reflections on possibilities for improvements in water management in the country. The study found a need to promote integrated action planning that is based on a strategic, participatory and decentralized character in water management; capable of creating an environment that reinforces the development of new institutional arrangements with the potential for absorption and implementation of its other assumptions, highlighting the relevance of an open and participatory decision-making process, regarding the management of water resources.